GIANT CLEAR CELL RENAL CARCINOMA: A CASE REPORT - Palgunadi, I Nyoman; Pramod, Sawkar Vijay (Indonesian Urological Association, 2018)
Objective: This article is aimed to report an unusual presentation of renal cancer T4N0M0 in which the tumor weighed about 5 kilograms in a patient admitted to Urology Department of Hasan Sadikin Hospital in Bandung, Indonesia, in August 2016. Case presentation: We report a case 62 year old male with history of growing mass in his left abdominal. There are also painless hematuria and weight loss of approximately 10 kg over the past 2 years. Discussion: Physical examination found a significant palpable, immobile and mild tender mass in the left upper quadrant of the abdomen. Abdominal Pelvic Computed Tomography (CT) scan revealed inhomogenous hypodens mass in the left kidney. Resection of the tumor revealed a 5 kg (22 x 25 x 18 cm, with total volume of 9.900 cm3) encapsulated neoplasm. Histophatological examination revealed a clear cell type renal cell carcinoma (RCC) with positive margin and Fuhrmann grade 2. In Asia, a giant chromophobe RCC exceeding 10 kg in weight was reported in 2009. As for previously reported giant clear cell RCC, we found out the data to be very limited. Conclusion: Giant RCC is rare, especially clear cell type in histophatological result. The size of the tumor reported in this article is considered as the largest-sized giant clear cell RCC ever reported in Asia. The size of the tumor in this case presented several challenges in the operative settings. However, the outcome and six months post-operative follow-up of the patient was satisfying in which there was no presence of single symptom within the six-month follow-up period.